Big Russ and me father and son, lessons of life - Russert, Tim 1950-2008 (New York, N.Y. Miramax Books, 2004)
The author offers a memoir of life with his father, a proud World War II veteran, describing growing up in 1950s Buffalo, the influence of his Catholic upbringing, and the importance of hard work, responsibility, and patriotism.
My father's war -- South Buffalo -- Respect -- Work -- Faith -- Food -- Baseball -- Fatherhood -- Sister Kennedy -- Canisius High School -- Discipline -- 1968 -- Cars -- JCU and law school, too. -- Daniel Patrick Moynihan -- Washington -- Politics -- Totus Tuus -- Meet the press -- Loss -- The Bills.
Date of publication obtained by calling the publisher.
KAL-3338, donated by Prof. Thomas David F. Chavez.
Keywords: Russert, Tim -- 1950-2008.; Russert, Tim -- 1924-2009.; Television journalists -- United States -- Biography; Fathers and sons -- New York (State) -- Buffalo -- Biography